Heme Induction with Delta-Aminolevulinic Acid Stimulates an Increase in Water and Electrolyte Excretion. (23rd January 2012) - Quadri, Syed; Jackson, Debra W.; Prathipati, Priyanka; Dean, Courtney; Jackson, Keith E.
Abstract : Purpose . Studies were performed to examine hemodynamic and renal function before and after acute induction of the endogenous CO system with delta-aminolevulinic acid (DALA), which drives HO activity. Methods . In vivo studies were conducted on Inactin-anesthetized male Sprague Dawley rats (250–300 g) either with or without chronic pretreatment with L-NAME (50 mg/Kg, q12 hours x4d). Results . DALA (80 μmol/Kg, IV bolus) administration acutely increased endogenous CO production and HO-1 protein. In untreated and L-NAME-pretreated rats, DALA did not alter BP, GFR, or RBF but increased UF, U Na V, and U K V (untreated: Δ108.8 ± 0.28%, 172.1 ± 18.4%, and 165.2 ± 45.9%; pretreated: Δ109.4 ± 0.29%, 187.3 ± 26.9%, and 197.2 ± 45.7%). Acute administration of biliverdin (20 mg/kg, IV) and bilirubin (30 mg/kg, IV) to similarly treated animals did not alter UF, U Na V, and U K V . Conclusion . These results demonstrate that heme oxygenase induction increases urine and electrolyte excretion and suggest a direct tubular action of endogenous carbon monoxide.